2020
DOI: 10.3390/plants9101362
|View full text |Cite
|
Sign up to set email alerts
|

Profiling Volatile Terpenoids from Calabrian Pine Stands Infested by the Pine Processionary Moth

Abstract: Terpenoids make up the biggest and most diversified class of chemical substances discovered in plants, encompassing over 40,000 individual compounds. In conifers, the production of terpenoids, either as oleoresin or emitted as volatile compounds, play an important role in the physical and chemical defence responses against pathogens and herbivores. In the present work, we examined, for the first time to the best of our knowledge, the terpenic defensive relations of Calabrian pine (Pinus nigra subsp. laricio (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…Most of the existing knowledge concerning the genetics and metabolism of specialized diterpenes in gymnosperms was obtained from model Pinaceae species, such as Picea glauca, Abies grandis, Pinus taeda, and P. contorta [1,2,22], for which large transcriptomic and genomic resources are available, as well as, in recent times, from species occupying key position in the gymnosperm phylogeny, such as those belonging to the Cupressaceae and the Taxaceae families [3,23]. In previous works of ours [20,26], we began to gain insight into the ecological and functional roles of the terpenes produced by the non-model conifer Pinus nigra subsp. laricio (Poiret) (Calabrian pine), one of the six subspecies of P. nigra (black pine) and an insofar completely neglected species under such respect.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the existing knowledge concerning the genetics and metabolism of specialized diterpenes in gymnosperms was obtained from model Pinaceae species, such as Picea glauca, Abies grandis, Pinus taeda, and P. contorta [1,2,22], for which large transcriptomic and genomic resources are available, as well as, in recent times, from species occupying key position in the gymnosperm phylogeny, such as those belonging to the Cupressaceae and the Taxaceae families [3,23]. In previous works of ours [20,26], we began to gain insight into the ecological and functional roles of the terpenes produced by the non-model conifer Pinus nigra subsp. laricio (Poiret) (Calabrian pine), one of the six subspecies of P. nigra (black pine) and an insofar completely neglected species under such respect.…”
Section: Introductionmentioning
confidence: 99%
“…This notwithstanding, studying those less represented monoterpenes at the molecular levels could be worthwhile, because some of them could undergo inductive dynamics in response to a wealth of environmental cues. As a matter of fact, in a previous work of ours conducted on adult individuals of P. laricio thriving in the same environment of the present study [ 27 ], we found that the foliar emissions of bornyl acetate and, to a lesser extent, of β-ocimene, differentiated plants infested by the caterpillars of the pine processionary moth ( Thaumetopoea pityocampa ) from their respective non-infested controls, being higher in the former during the period of maximal trophic activity of the larvae. On such basis, we are currently pursuing the isolation of FL cDNAs coding for the enzymes responsible for producing limonene, bornyl acetate, and α-tujene in P. laricio , to decipher their possible functional and ecological roles in plant–environment biotic and abiotic interactions.…”
Section: Resultsmentioning
confidence: 67%
“…One possible explanation could be that, in the needles, monoterpenes are not only components of oleoresin, but are also actively emitted as volatile compounds to execute the well-known array of physiological and ecological functions in plant-to-environment interactions (see Introduction). As a matter of fact, in a previous study of ours conducted on adult individuals of P. laricio thriving in the same natural context of the present study [ 27 ], we adopted the “headspace” GC–MS approach to collect volatile terpenoids emitted from vegetation, and we found that, together with a ten of different sesquiterpenes, at least half of the same monoterpenes reported in Figure 1 , namely, bornyl acetate, limonene, myrcene, β-phellandrene, α- and β-pinene, and α-terpineol, were persistently and consistently present in the blend of volatiles released by the young needles throughout their growing season, with β-phellandrene and α- and β-pinene being the major components on a comparative basis.…”
Section: Resultsmentioning
confidence: 69%
See 1 more Smart Citation
“…The final original article was focused on the chemical profiling of volatiles released from pine stands infested by the pine processionary moth [ 21 ]. The work aimed to understand the variations induced by the infestations and identify those metabolites with a protective activity.…”
mentioning
confidence: 99%